A puncture-resistant self-repairing tire inner liner rubber and a method of making the same
Patent Information
- Application Number
- CN202611180907.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]为此,本发明提供一种耐刺扎自修复轮胎内衬层橡胶及其制备方法,以解决现有技术中存在的不足
(1)自修复功能与内衬层本体一体化
Smart Images

Figure CN122978607A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire manufacturing technology, specifically to a puncture-resistant self-healing tire inner liner rubber and its preparation method. Background Technology
[0002] The tire inner liner, located inside the tire carcass ply, primarily functions to maintain internal pressure and prevent gas leakage. Current technology generally uses butyl rubber, known for its excellent airtightness, as the main material. With the development of the automotive industry, the requirements for tire safety and durability are increasingly stringent, especially the self-healing function that allows the tire to maintain its driving ability after being punctured by a sharp object, which has become a hot research topic in the industry.
[0003] Chinese patent CN114058293A discloses a self-healing tire sealant and its preparation method. The method uses butyl rubber, conjugated diene rubber, reinforcing filler, liquid olefin compound, resin, and vulcanizing agent as components. These components are premixed in an internal mixer, and then the liquid olefin and vulcanizing agent are added and mixed through an extruder to obtain the sealant, which is then coated onto the inner surface of the tire to achieve puncture self-repair. This method has three shortcomings: First, the liquid olefin compound is added all at once in the extruder, and due to the large viscosity difference and limited compatibility with the solid rubber, uneven dispersion or localized enrichment is likely to occur, leading to unstable self-healing performance. Second, the sealant is attached to the inner liner surface as an independent coating, resulting in limited adhesion to the matrix. Long-term use and high-temperature, high-speed conditions pose risks of peeling and flow, affecting tire balance and the durability of self-healing. Third, the vulcanizing agent is added in a conventional manner, lacking control over the synergistic release of the vulcanizing agent and other components, and the uniformity of the crosslinking network needs improvement.
[0004] Chinese patent CN120310149A discloses an inner lining rubber composition comprising a transition layer and an airtight layer rubber, with the addition of metal powder (e.g., iron powder) to improve thermal conductivity and airtightness, and employing a segmented mixing process using an internal mixer. This technology primarily focuses on thermal conductivity and airtightness, without addressing self-healing capabilities; the metal powder is added alone without forming an effective synergy with the vulcanization system, and its catalytic effect fails to work in conjunction with vulcanization accelerators; furthermore, conventional high-temperature vulcanization processes result in a contradiction between the crosslinking network formation rate and the stability of the liquid components.
[0005] In summary, existing technologies either employ surface coatings to add self-healing functions, which suffer from insufficient adhesion and potential flow problems; or they only optimize thermal conductivity and airtightness without imparting self-healing capabilities. There is still a lack of a systematic solution that organically integrates self-healing functions with the inner lining layer itself and achieves component gradient distribution and uniform control of cross-linked networks through refined processes.
[0006] This invention provides a method for preparing puncture-resistant self-healing tire inner liner rubber. By integrating the self-healing function with the inner liner body and achieving gradient distribution of self-healing components and uniform control of crosslinking network through refined process design, it aims to overcome the problems of uneven dispersion of liquid components, poor coating adhesion and insufficient crosslinking uniformity in the prior art, thereby improving the self-healing stability, durability and overall performance of the inner liner. Summary of the Invention
[0007] Therefore, the present invention provides a puncture-resistant self-healing tire inner liner rubber and its preparation method to overcome the shortcomings of the prior art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a method for preparing puncture-resistant self-healing tire inner liner rubber is provided, comprising the following steps: S1. After mixing butyl rubber and conjugated diene rubber, plasticize for 2-4 minutes, add reinforcing filler, resin and homogenizer, mix at 100-130℃ for 5-8 minutes, discharge the rubber, and obtain masterbatch. S2. Cool the masterbatch obtained in step S1 to 40-60℃, add 30%-50% of the total amount of liquid olefin compounds, and keep it warm while stirring for 20-40 minutes; heat the system to 80-100℃, add the remaining liquid olefin compounds, and continue to mix for 10-20 minutes to obtain the pre-dispersed rubber compound. S3. Add vulcanizing agent and composite vulcanizing package to the pre-dispersed rubber compound obtained in step S2, and mix at 60-80℃ for 3-5 minutes to obtain two-stage compounded rubber. S4. The two-stage compound obtained in step S3 is left to stand for 8-24 hours at a temperature of 20-30℃ and a relative humidity of 40%-60%. Finally, it is vulcanized for 60-120 minutes at a pressure of 0.5-2MPa and a temperature of 70-90℃ to obtain puncture-resistant self-healing tire inner liner rubber.
[0009] Further, the composite vulcanizing package mentioned in step S3 is prepared by mechanically mixing metal oxide powder and vulcanization accelerator at a mass ratio of (2-10):(1-5) for 5-10 minutes at room temperature.
[0010] Furthermore, the puncture-resistant self-healing tire inner liner rubber is composed of the following parts by weight of raw materials: 80-100 parts of butyl rubber; 0-20 parts of conjugated diene rubber; 50-500 parts of liquid olefin compounds; 3-15 parts of composite vulcanizing package; 1-15 parts of vulcanizing agent; 0-50 parts of resin; 5-70 parts of reinforcing filler; 2-8 parts homogenizer.
[0011] Furthermore, the liquid olefin compound is selected from one or more of polyisobutylene, polyisoprene, or polybutadiene.
[0012] Furthermore, the number-average molecular weight of the liquid olefin compound is 500-5000 g / mol.
[0013] Further, the metal oxide powder is selected from one or more of zinc oxide, magnesium oxide, or calcium oxide; the vulcanization accelerator is selected from one or more of thiuram accelerators (e.g., accelerator TMTD), thiazole accelerators (e.g., accelerator DM), or sulfenamide accelerators (e.g., accelerator CBS).
[0014] Furthermore, the particle size D50 of the metal oxide powder is 0.5-5 μm.
[0015] Furthermore, the metal oxide powder is zinc oxide; the sulfidation accelerator is a sulfenamide accelerator (e.g., accelerator CBS).
[0016] Further, the conjugated diene rubber is selected from one or more of natural rubber, butadiene rubber, polyisoprene rubber, or styrene-butadiene rubber; the vulcanizing agent is sulfur (e.g., insoluble sulfur HD OT20); the resin is selected from one or more of C5 resin, C9 resin, C5 / C9 resin, rosin resin, terpene resin, DCPD resin, phenolic resin, or coumarone-indene resin; the reinforcing filler is selected from one or more of carbon black or silica; the homogenizer is selected from one or more of aromatic hydrocarbon resin mixtures (e.g., Struktol® 40 MS Flakes), aliphatic hydrocarbon resin mixtures (e.g., Struktol® 60 NSFlakes), or aromatic-aliphatic hydrocarbon blends (e.g., homogenizer H40MSF).
[0017] Furthermore, the conjugated diene rubber is natural rubber; the resin is C5 resin; the reinforcing filler is carbon black and silica; and the homogenizer is an aromatic hydrocarbon resin mixture (e.g., Struktol® 40 MS Flakes).
[0018] According to a second aspect of the present invention, the application of the puncture-resistant self-healing tire inner liner rubber prepared by the aforementioned method in tire production is provided.
[0019] Compared with the prior art, the present invention has the following advantages: (1) Self-healing function integrated with the inner lining body This invention integrates a self-healing liquid olefin component directly into the inner liner rubber matrix, rather than as a separate coating applied to the surface. Its mechanism of action lies in the stepwise adsorption and swelling treatment of the liquid olefin, forming a gradient distribution within the rubber network and creating a continuously transitioning interface layer between the liquid olefin and the rubber matrix. This structure eliminates the physical interface between the coating and the matrix, preventing interfacial peeling and overall coating flow caused by temperature changes and centrifugal forces during long-term use. Flowability index tests show that the anti-flow capability of this embodiment is higher than that of Comparative Example 1 (difference of 15-50), demonstrating the morphological stability of the integrated structure under high-temperature and high-speed operating conditions.
[0020] (2) Liquid olefin gradient distribution structure This invention employs a stepwise processing technique involving low-temperature adsorption and high-temperature dispersion to create a gradient distribution of liquid olefins within a rubber matrix, characterized by surface enrichment and moderate internal distribution. The formation mechanism is as follows: during the low-temperature stage (40-60℃), the high viscosity of the liquid olefins tends to cause them to remain on the rubber surface, resulting in surface enrichment; during the high-temperature stage (80-100℃), the viscosity of the liquid olefins decreases, and their molecular mobility increases, gradually diffusing inwards to form a concentration gradient from the surface to the interior. The surface-enriched liquid components can migrate to the damaged site upon puncture, achieving sealing (gas retention rate of 91%-98%); the uniformly dispersed liquid components in the interior provide a reserve for long-term self-healing function (liquid retention rate of 88%-95% after thermal aging). This gradient structure balances the speed of self-healing response with functional durability.
[0021] (3) Metal oxide-accelerator composite vulcanization package This invention pre-composites metal oxide powder with a vulcanization accelerator to form a composite vulcanization package with a carrier-active component structure. Its controlled-release mechanism lies in the physical adsorption of accelerator molecules by the metal oxide, fixing the accelerator to the oxide surface during the initial mixing stage, rather than allowing it to disperse freely in the rubber compound. As the temperature rises and shear forces persist during mixing and vulcanization, the accelerator gradually desorbs and releases from the oxide surface, achieving a sequential supply of vulcanization activity. This mechanism allows the crosslinking reaction to proceed smoothly, resulting in a relative increase in crosslinking density of 15%-35%, improved crosslinking network uniformity, and simultaneous improvement in mechanical properties and structural stability.
[0022] (4) Static curing and long-term low-temperature vulcanization under pressure This invention employs a static curing step before vulcanization and a pressurized, low-temperature, long-duration vulcanization process. The synergistic mechanism lies in the following: the curing stage (20-30℃, 8-24h) provides relaxation time for internal stresses introduced during mixing, while the liquid components continue to diffuse and migrate under the drive of the concentration gradient, stabilizing the gradient distribution structure; low-temperature vulcanization (70-90℃) reduces the crosslinking reaction rate, allowing the vulcanized network to be gradually built, reducing local network defects and liquid olefin volatilization losses caused by excessively rapid crosslinking reactions under high-temperature conditions; and the pressurized conditions (0.5-2MPa) inhibit the vaporization and expansion of volatiles during vulcanization, reducing internal bubbles and pores in the product and improving density. This process combination ensures sufficient crosslinking while improving liquid retention by 13%-22% compared to the traditional high-temperature process (Comparative Example 1).
[0023] (5) Strong process adaptability and economy This invention adjusts the process based on existing self-healing sealant formulations, using commercially available products in the rubber processing industry, including liquid olefins, metal oxides, and accelerators. The preparation process can be implemented on existing internal mixers and vulcanizing equipment, eliminating the need for specialized coating equipment or production line modifications, thus keeping overall production costs under control. This invention provides a widely applicable technical solution for the integrated preparation of self-healing tire inner liner layers. Attached Figure Description
[0024] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0025] The structures, proportions, sizes, etc. illustrated in this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed herein, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.
[0026] Figure 1 This is a flowchart illustrating the process for preparing the puncture-resistant self-healing tire inner liner rubber of this invention. Detailed Implementation
[0027] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] According to a first aspect of the present invention, a method for preparing puncture-resistant self-healing tire inner liner rubber is provided, comprising the following steps (the preparation process flow is as follows): Figure 1 (as shown) S1. After mixing butyl rubber and conjugated diene rubber, plasticize for 2-4 minutes, add reinforcing filler, resin and homogenizer, mix at 100-130℃ for 5-8 minutes, discharge the rubber, and obtain masterbatch. S2. Cool the masterbatch obtained in step S1 to 40-60℃, add 30%-50% of the total amount of liquid olefin compounds, and keep it warm while stirring for 20-40 minutes; heat the system to 80-100℃, add the remaining liquid olefin compounds, and continue to mix for 10-20 minutes to obtain the pre-dispersed rubber compound. S3. Add vulcanizing agent and composite vulcanizing package to the pre-dispersed rubber compound obtained in step S2, and mix at 60-80℃ for 3-5 minutes to obtain two-stage compounded rubber. S4. The two-stage compound obtained in step S3 is left to stand for 8-24 hours at a temperature of 20-30℃ and a relative humidity of 40%-60%. Finally, it is vulcanized for 60-120 minutes at a pressure of 0.5-2MPa and a temperature of 70-90℃ to obtain puncture-resistant self-healing tire inner liner rubber.
[0029] Further, in step S3, the composite vulcanizing package is prepared by mechanically mixing metal oxide powder and vulcanization accelerator at a mass ratio of (2-10):(1-5) for 5-10 minutes at room temperature.
[0030] Furthermore, the puncture-resistant self-healing tire inner liner rubber is composed of the following parts by weight of raw materials: 80-100 parts of butyl rubber; 0-20 parts of conjugated diene rubber; 50-500 parts of liquid olefin compounds; 3-15 parts of composite vulcanizing package; 1-15 parts of vulcanizing agent; 0-50 parts of resin; 5-70 parts of reinforcing filler; 2-8 parts homogenizer.
[0031] Furthermore, the liquid olefin compound is selected from one or more of polyisobutylene, polyisoprene, or polybutadiene.
[0032] Furthermore, the number-average molecular weight of liquid olefin compounds is 500-5000 g / mol.
[0033] Furthermore, the metal oxide powder is selected from one or more of zinc oxide, magnesium oxide, or calcium oxide; the sulfidation accelerator is selected from one or more of thiuram accelerators (e.g., accelerator TMTD), thiazole accelerators (e.g., accelerator DM), or sulfenamide accelerators (e.g., accelerator CBS).
[0034] Furthermore, the particle size D50 of the metal oxide powder is 0.5-5 μm.
[0035] Furthermore, the metal oxide powder is zinc oxide; the sulfidation accelerator is a sulfenamide accelerator.
[0036] Further, the conjugated diene rubber is selected from one or more of natural rubber, butadiene rubber, polyisoprene rubber, or styrene-butadiene rubber; the vulcanizing agent is sulfur (e.g., insoluble sulfur HD OT20); the resin is selected from one or more of C5 resin, C9 resin, C5 / C9 resin, rosin resin, terpene resin, DCPD resin, phenolic resin, or coumarone-indene resin; the reinforcing filler is selected from one or more of carbon black or silica; the homogenizing agent is selected from one or more of aromatic hydrocarbon resin mixtures (e.g., Struktol® 40 MS Flakes), aliphatic hydrocarbon resin mixtures (e.g., Struktol® 60 NS Flakes), or aromatic-aliphatic hydrocarbon blends (e.g., homogenizing agent H40MSF).
[0037] Furthermore, the conjugated diene rubber is natural rubber; the resin is C5 resin; the reinforcing filler is carbon black and silica; and the homogenizer is a mixture of aromatic hydrocarbon resins (e.g., Struktol® 40 MS Flakes).
[0038] According to a second aspect of the present invention, the application of the puncture-resistant self-healing tire inner liner rubber prepared by the preparation method is provided in tire production.
[0039] The reagents used in this invention are as follows: Butyl rubber (Yanshan Petrochemical IIR1751), purchased from Shanghai Sanlian Industrial Co., Ltd.; Liquid polyisobutylene (Oppanol® B 50, BASF, Germany) was purchased from Shanghai Kaiyin Chemical Co., Ltd. Aromatic hydrocarbon resin mixture (Struktol® 40 MS Flakes), purchased from Jiatuo (Shanghai) Chemical Trading Co., Ltd.; The sulfenamide accelerator (accelerator CBS) was purchased from Greenlink (Jining) Chemical Technology Co., Ltd. Insoluble sulfur HD OT20 was purchased from Shandong Shangshun Chemical Co., Ltd. Carbonyl iron powder (particle size D50=1μm, purity ≥99.9%) was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd. The remaining raw materials are all commercially available products commonly used in the rubber processing industry.
[0040] The equipment used in this invention is as follows: Mooney viscosity tester, equipped with a large rotor (L-type, 38.1 mm in diameter, 5.5 mm thick). Constant temperature forced-air drying oven (temperature control accuracy ±1℃, temperature uniformity ±2℃); Analytical balance (accuracy 0.1 mg); Dryer (containing color-changing silica gel desiccant); Stainless steel mesh bag (0.074mm aperture, 200 mesh); Ground glass stoppered wide-mouth bottle (100mL capacity); Vacuum drying oven (temperature control accuracy ±1℃); The thermal conductivity meter (Netzsch HFM 436, Germany) consists of a hot plate, a cold plate, a heat flow sensor, and a temperature control system.
[0041] To better illustrate the technical effects of this invention, the following embodiments are provided.
[0042] In the following examples, Examples 1 and 2 are implementations within the preferred formulation range of the present invention; in Example 3, the amount of liquid olefins is at the upper limit (500 parts), used to verify the process feasibility of the high liquid content system; in Example 4, the amount of liquid olefins is at the lower limit (50 parts), used to verify the process feasibility of the low liquid content system. All examples employ the same stepwise adsorption and low-temperature long-time sulfidation process.
[0043] Example 1 The preparation method of the puncture-resistant self-healing tire inner liner rubber in this embodiment is as follows: S1. Mix 8kg of Yanshan Petrochemical IIR1751 with 2kg of natural rubber, masticate for 3 minutes, add 2.5kg of carbon black, 2kg of silica, 1.2kg of C5 petroleum resin and 0.5kg of Struktol® 40 MS Flakes, mix at 115℃ for 6 minutes, discharge the rubber, and obtain the masterbatch. S2. Cool the masterbatch obtained in step S1 to 50°C, add 14 kg of BASF Oppanol® B 50 from Germany, and keep it warm while stirring for 30 min; heat the system to 90°C, add 21 kg of BASF Oppanol® B 50 from Germany, and continue mixing for 15 min to obtain the pre-dispersed rubber compound. S3. Add 1 kg of insoluble sulfur HD OT20 and 0.85 kg of composite vulcanizing bag (obtained by mechanically mixing 0.6 kg of zinc oxide and 0.25 kg of accelerator CBS at room temperature for 8 min) to the pre-dispersed rubber compound obtained in step S2, and mix at 70°C for 4 min to obtain the two-stage compound. S4. The two-stage compound obtained in step S3 is left to stand for 16 hours at a temperature of 25°C and a relative humidity of 50%. Finally, it is vulcanized for 90 minutes at a pressure of 1.5MPa and a temperature of 80°C to obtain puncture-resistant self-healing tire inner liner rubber.
[0044] Example 2 The preparation method of the puncture-resistant self-healing tire inner liner rubber in this embodiment is as follows: S1. Mix 9kg of Yanshan Petrochemical IIR1751 with 1kg of natural rubber, masticate for 3 minutes, add 3kg of carbon black, 2kg of silica, 1kg of C5 petroleum resin and 0.5kg of Struktol® 40 MS Flakes, mix at 115℃ for 6 minutes, discharge the rubber, and obtain the masterbatch. S2. Cool the masterbatch obtained in step S1 to 50°C, add 12kg of BASF Oppanol® B 50 from Germany, and keep it warm while stirring for 30 minutes; raise the temperature of the system to 90°C, add 18kg of BASF Oppanol® B 50 from Germany, and continue mixing for 15 minutes to obtain the pre-dispersed rubber compound. S3. Add 1.2 kg of insoluble sulfur HD OT20 and 0.7 kg of composite vulcanizing bag (obtained by mechanically mixing 0.5 kg of zinc oxide and 0.2 kg of accelerator CBS at room temperature for 8 min) to the pre-dispersed rubber compound obtained in step S2, and mix at 70°C for 4 min to obtain the two-stage compound; S4. The two-stage compound obtained in step S3 is left to stand for 16 hours at a temperature of 25°C and a relative humidity of 50%. Finally, it is vulcanized for 90 minutes at a pressure of 1.5MPa and a temperature of 80°C to obtain puncture-resistant self-healing tire inner liner rubber.
[0045] Example 3 The preparation method of the puncture-resistant self-healing tire inner liner rubber in this embodiment is as follows: S1. Pulverize 10kg of Yanshan Petrochemical II R1751 for 3 minutes, add 3.5kg of carbon black, 3.5kg of silica and 0.8kg of Struktol® 40 MS Flakes and mix evenly. Knead at 115℃ for 6 minutes, remove the glue, and obtain the masterbatch. S2. Cool the masterbatch obtained in step S1 to 50°C, add 15kg of BASF Oppanol® B 50 from Germany, and keep it warm while stirring for 30 minutes; heat the system to 90°C, add 35kg of BASF Oppanol® B 50 from Germany, and continue mixing for 15 minutes to obtain the pre-dispersed rubber compound. S3. Add 1.5 kg of insoluble sulfur HD OT20 and 1.5 kg of composite vulcanizing bag (obtained by mechanically mixing 1.0 kg of zinc oxide and 0.5 kg of accelerator CBS at room temperature for 8 min) to the pre-dispersed rubber compound obtained in step S2, and mix at 70°C for 4 min to obtain the two-stage compound. S4. The two-stage compound obtained in step S3 is left to stand for 16 hours at a temperature of 25°C and a relative humidity of 50%. Finally, it is vulcanized for 90 minutes at a pressure of 1.5MPa and a temperature of 80°C to obtain puncture-resistant self-healing tire inner liner rubber.
[0046] Example 4 The preparation method of the puncture-resistant self-healing tire inner liner rubber in this embodiment is as follows: S1. Mix 8kg of Yanshan Petrochemical II R1751 with 2kg of natural rubber, masticate for 3 minutes, add 0.3kg of carbon black, 0.2kg of silica, 5kg of C5 petroleum resin and 0.2kg of Struktol® 40 MS Flakes, mix at 115℃ for 6 minutes, discharge the rubber, and obtain the masterbatch. S2. Cool the masterbatch obtained in step S1 to 50°C, add 1.5 kg of BASF Oppanol® B 50 from Germany, and keep it warm while stirring for 30 min; heat the system to 90°C, add 3.5 kg of BASF Oppanol® B 50 from Germany, and continue mixing for 15 min to obtain the pre-dispersed rubber compound; S3. Add 0.1 kg of insoluble sulfur HD OT20 and 0.3 kg of composite vulcanizing bag (obtained by mechanically mixing 0.2 kg of zinc oxide and 0.1 kg of accelerator CBS at room temperature for 8 min) to the pre-dispersed rubber compound obtained in step S2, and mix at 70°C for 4 min to obtain the two-stage compound; S4. The two-stage compound obtained in step S3 is left to stand for 16 hours at a temperature of 25°C and a relative humidity of 50%. Finally, it is vulcanized for 90 minutes at a pressure of 1.5MPa and a temperature of 80°C to obtain puncture-resistant self-healing tire inner liner rubber.
[0047] Comparative Example 1 The preparation method of the tire inner liner rubber in this comparative example is as follows: S1. Mix 9kg of Yanshan Petrochemical IIR1751 with 1kg of natural rubber, masticate for 3 minutes, add 3kg of carbon black, 2kg of silica, 1kg of C5 petroleum resin and 0.5kg of Struktol® 40 MS Flakes, mix at 115℃ for 6 minutes, discharge the rubber, and obtain the masterbatch. S2. Cool the masterbatch obtained in step S1 to 50°C, add 35kg of BASF Oppanol® B 50 from Germany, and keep it warm while stirring for 30min; heat the system to 90°C and continue mixing for 15min (all liquid olefins are added at once, without gradient distribution) to obtain the pre-dispersed rubber compound; S3. Add 1.5 kg of insoluble sulfur HD OT20, 0.6 kg of zinc oxide and 0.25 kg of accelerator CBS to the pre-dispersed rubber compound obtained in step S2 in sequence (the vulcanizing components are added separately, no composite vulcanizing package is prepared in advance, and there is no slow-release effect), and mix at 70°C for 4 min to obtain the two-stage compound. S4. The two-stage compound obtained in step S3 is vulcanized at a pressure of 1.5 MPa and a temperature of 80°C for 90 minutes to obtain tire inner liner rubber.
[0048] Comparative Example 2 The preparation method of the tire inner liner rubber in this comparative example is as follows: S1. Mix 9 kg of Yanshan Petrochemical II R1751 with 1 kg of natural rubber, plasticize for 3 min, add 3 kg of carbon black, 2 kg of silica, 1 kg of C5 petroleum resin and 0.5 kg of Struktol® 40 MS Flakes, mix at 130℃ for 100 min, discharge the glue, and obtain mixture P. S2. Using an extruder, the mixture P obtained in step S1, 30 kg of BASF Oppanol (Germany) is processed. ® B 50, 1.5 kg of dicumyl peroxide, and 0.6 kg of zinc oxide are mixed at 90°C to obtain a self-repairing sealant. S3. Apply the self-healing sealant obtained in step S2 to the inner surface of the tire to form a tire inner liner rubber with a self-healing coating.
[0049] Comparative Example 3 The preparation method of the tire inner liner rubber in this comparative example is as follows: S1. Mix 6 kg of brominated butyl rubber with 4 kg of natural rubber and pressurize in a mixer (18 MPa, 1 min) to obtain pressurized rubber. S2. After adding 1 kg of chlorosulfonated polyethylene rubber to the pressurized rubber obtained in step S1, raise the press and add 6 kg of carbon black, 2.5 kg of silica, 1.2 kg of C5 petroleum resin, 0.5 kg of Struktol® 40 MS Flakes, 1.2 kg of insoluble sulfur HD OT20, 0.4 kg of carbonyl iron powder and 1.5 kg of accelerator CBS in sequence. Mix at 70°C for 4 min to obtain the compound. S3. Stir the mixture obtained in step S2 for 45 seconds and then discharge the rubber to obtain an airtight rubber composition. S4. The airtight layer rubber composition obtained in step S3 is vulcanized at a pressure of 1.5 MPa and a temperature of 80°C for 90 min to obtain the tire inner liner rubber.
[0050] Test Example 1 Self-healing and sealing performance To evaluate the self-healing and sealing performance of the puncture-resistant self-healing tire inner liner rubber of the present invention, the air retention rate of the puncture-resistant self-healing tire inner liner rubber in Examples 1-4 and the tire inner liner rubber in Comparative Examples 1-3 was tested. The specific test methods are as follows: The air retention rate test simulates the immediate sealing ability of the self-healing rubber compound in the inner liner of a tire after it has been punctured by a sharp object during actual use. Compressed air is injected into the sealed cavity, and the change in air pressure before and after puncture is recorded. The air pressure retention rate characterizes the repair effect of the rubber compound on the puncture damage. A higher air retention rate indicates that the rubber compound can quickly seal the puncture and prevent gas leakage after puncture.
[0051] A tire airtightness testing fixture is used, which consists of an upper chamber, a lower chamber, a sealing ring, and a pressure sensor. The upper chamber is a closed pressurization chamber, and the lower chamber is an open sample support chamber. The upper and lower chambers are fastened together by a flange, and the sample is placed between them. The pressure sensor (range 0-500 kPa, accuracy ±0.5% FS) is installed at the gas inlet of the upper chamber for real-time monitoring of the chamber pressure. The upper chamber is connected to an inflation valve and a pressure relief valve.
[0052] Take the fully vulcanized puncture-resistant self-healing tire inner liner rubber from each experimental group and cut it into circular pieces with a diameter of 100 mm and a thickness of 2 mm. Five parallel samples are prepared for each group. The sample surface should be flat, free of bubbles, and without visible defects. Before testing, acclimate the samples to room temperature (23±2℃) and relative humidity (50±5%) for 24 hours. Conduct the test according to the following steps: Place the disc sample between the upper and lower cavities of the test fixture, and ensure airtightness after tightening the flange; Close the pressure relief valve, open the inflation valve, and fill the upper chamber with compressed air to the initial pressure. P 0 = 200 kPa (gauge pressure); Close the inflation valve and hold for 30 seconds. Observe whether the air pressure sensor reading is stable to confirm that there is no leakage. Using a standard steel needle with a diameter of 2 mm (needle tip cone angle of 30°), vertically pierce the center of the sample at a speed of 50 mm / min. After penetrating the sample, the steel needle continues to advance 5 mm, pauses for 5 seconds, and then is pulled out at the same speed. Immediately after puncture, seal the test device and allow it to stand at room temperature (23±2℃) for 24 hours; Read the barometric pressure sensor reading after 24 hours. P 24 (Unit: kPa).
[0053] Calculate the gas retention rate (%) using the following formula: ; in, P 0 represents the initial air pressure in the superior cavitary space before puncture, in kPa (gauge pressure). In this test... P 0 = 200 kPa; P 24 The pressure in the upper cavity is indicated in kPa (gauge pressure) after 24 hours of rest at room temperature following puncture.
[0054] Take the arithmetic mean as the final result.
[0055] The test results are shown in Table 1 below: Table 1. Test results of gas retention rate of samples in each experimental group.
[0056] Note: A higher gas retention rate indicates better self-healing sealing performance after puncture. Comparative Group 3 did not contain liquid olefins and therefore lacked self-healing capabilities; therefore, gas retention rate testing was not performed.
[0057] It can be seen from Table 1 above: The gas retention rates of the samples in Examples 1-4 were 98%, 96%, 97%, and 91%, respectively, all superior to Comparative Example 1 (85%). Among them, Examples 1-3 were superior to Comparative Example 2 (92%), while Example 4 (91%) was lower than Comparative Example 2 (92%). The improvement in gas retention rate is mainly attributed to the construction of the liquid olefin gradient distribution structure: the liquid components enriched on the surface can respond quickly and migrate to the damaged site when puncture occurs, achieving efficient sealing; the uniformly dispersed liquid components inside provide reserves for long-term self-healing function.
[0058] Comparative Example 1 uses a traditional internal mixer for one-time mixing, with all components added simultaneously. Liquid olefins cannot form a gradient distribution in the rubber matrix, resulting in uneven dispersion, local enrichment, or seepage. After puncture, the repair components cannot migrate to the damaged site in time, thus resulting in the lowest gas retention rate (85%).
[0059] Although Comparative Example 2 employed a combination of internal mixer and extruder, the liquid olefins were still added in a single step during extrusion, failing to establish a gradient distribution structure. Furthermore, this comparative example used a peroxide vulcanization system (diisopropylbenzene peroxide), with the vulcanizing agent added simultaneously with the liquid olefins, lacking control over the vulcanization reaction sequence. Simultaneously, the sealant was applied as a coating to the inner surface of the tire, creating a physical interface with the inner liner, posing a risk of flow or peeling during long-term use. Therefore, although the strong shearing action of the extruder resulted in better liquid dispersion uniformity than a single-step mixing process using an internal mixer (Comparative Example 1), and its gas retention rate (92%) was higher than Comparative Example 1 (85%) and Example 4 (91%), the lack of an immediate response advantage from the gradient distribution structure and the limitation of the coating method on the durability of the self-healing function resulted in a lower gas retention rate than Examples 1-3 (96%-98%), which employed a gradient distribution structure and integrated process.
[0060] Comparative group 3 did not contain liquid olefins and therefore lacked self-healing capabilities. After being punctured by a steel needle, the rubber compound could not self-repair and seal the puncture hole; therefore, no gas retention rate test was conducted.
[0061] Test Example 2 High temperature stability and durability To evaluate the high-temperature stability and durability of the puncture-resistant self-healing tire liner rubber of the present invention, the flowability index and liquid retention rate of the puncture-resistant self-healing tire liner rubber in Examples 1-4 and the tire liner rubber in Comparative Examples 1-3 were tested. The specific test methods are as follows: (1) Liquidity Index Test The flowability index is used to evaluate the ability of self-healing compounds to resist deformation and flow under high-temperature shear conditions. When self-healing tires are driven at high speeds, repeated flexing and deformation in the tire shoulder and center tread area generates heat, with temperatures potentially reaching 80-120°C. At this temperature, the viscosity of the liquid olefin component in the self-healing compound decreases, and the compound softens overall. Insufficient flow resistance can lead to creep, sagging, or uneven thickness distribution in the inner liner, affecting the tire's dynamic balance and service life.
[0062] According to GB / T 1232.1-2016 "Determination of Uncured Rubber Using a Disk Shear Viscometer - Part 1: Determination of Mooney Viscosity", a Mooney viscometer was used to apply continuous shear to the sample under high rotor speed and high temperature conditions. The change of torque with shear time was recorded, and the torque retention rate was used to characterize the anti-flow ability of the rubber compound under high temperature and high speed conditions.
[0063] Take the fully vulcanized puncture-resistant self-healing tire inner liner rubber from each experimental group and prepare circular specimens approximately 50 mm in diameter and 6 mm thick. Three parallel specimens are prepared for each group. The specimen surface should be flat, free of bubbles, and free of impurities. Conduct the tests according to the following steps: Preheat the Mooney viscometer test chamber to 120°C and maintain a constant temperature; Place the sample into the test chamber, close the mold cavity, and apply pressure; Set the rotor speed to 5 r / min (2 r / min for conventional Mooney viscosity testing). Start the test and continuously shear for 30 minutes, recording the torque value (unit: Mooney units) every 1 minute. Plot the torque-time curve and record the initial torque value. T Torque values at 0 (end of 1 minute) and 30 minutes T 30 .
[0064] Calculate the torque retention rate (%) and liquidity index using the following formulas: ; in, T 0 represents the initial torque value (MU) at the end of the first minute; T 30 This represents the torque value (MU) at the end of 30 minutes of continuous shearing.
[0065] ; Among them, the torque retention rate of the experimental group represents the torque retention rate (%) of each of the Examples 1-3 and Comparative Examples 1 and 3; the torque retention rate of the reference group represents the torque retention rate (%) of Comparative Example 2.
[0066] Take the arithmetic mean as the final result.
[0067] (2) Liquid retention rate test Liquid retention rate is used to evaluate the ability of liquid olefin components in self-healing rubber compounds to resist volatilization and migration under high-temperature conditions. During operation, the internal temperature of self-healing tires can reach 60-80°C or even higher, and the volatility of the liquid olefin components directly affects the durability of the self-healing function. If a large amount of liquid components volatilizes, the rubber compound will lose its fluidity and self-healing ability.
[0068] The retention rate of the liquid olefin component was calculated by measuring the mass change of the vulcanized rubber sample before and after heat aging using the thermal aging weight loss method. At 70℃, the volatilization of liquid olefins was the main source of mass loss, while the weight loss of the rubber matrix and fillers was negligible.
[0069] Take the fully vulcanized puncture-resistant self-healing tire inner liner rubber from each experimental group, prepare a sheet approximately 2 mm thick, and cut it into square specimens approximately 30 mm × 30 mm. Three parallel specimens should be prepared for each group. The specimens should have clean edges, be free of burrs, and have a clean surface. Conduct the tests according to the following steps: The sample was conditioned at room temperature (23±2℃) and relative humidity (50±5%) for 24 hours. Accurately weigh the initial mass of each sample. W 0 (unit: g, accurate to 0.1 mg); The samples were laid flat in a constant temperature drying oven, with no overlap between them, and the temperature was set to 70℃. After 72 hours of heat aging, the sample was removed and immediately placed in a desiccator to cool to room temperature (approximately 30 minutes).
[0070] Remove the sample from the desiccator and accurately weigh it after aging. W 1 (Unit: g, accurate to 0.1 mg).
[0071] Calculate the liquid retention rate (%) using the following formula: ; in, W 0 represents the initial mass (g) of the sample before thermal aging; W 1 represents the mass (g) of the sample after heat aging at 70℃ for 72 hours.
[0072] Take the arithmetic mean as the final result.
[0073] The test results are shown in Table 2 below: Table 2. Results of fluidity index and liquid retention rate tests for samples in each experimental group.
[0074] Note: Using Comparative Example 2 as the baseline value of 100, a higher flowability index indicates better shape stability and stronger anti-flow ability of the rubber compound under high-temperature shear conditions. A higher liquid retention rate indicates better stability of the liquid olefin component and stronger resistance to volatility and migration.
[0075] It can be seen from Table 2 above: The flowability indices of the samples in Examples 1-4 were 140, 135, 145, and 110, respectively, all superior to those of Comparative Example 1 (95) and Comparative Example 2 (100). Examples 1-3 were superior to Comparative Example 3 (120), while Example 4 (110) was inferior to Comparative Example 3 (120). The improvement in flowability index was mainly attributed to the gradient distribution structure of the liquid olefins ensuring a moderate surface liquid content, preventing excessive liquid migration under centrifugal force. Simultaneously, the uniform cross-linked network provided stronger skeletal support for the rubber matrix, suppressing overall flow deformation. The liquid retention rates were 94%, 92%, 95%, and 88%, respectively, all superior to those of Comparative Example 1 (78%) and Comparative Example 2 (82%). This improvement was mainly attributed to the low-temperature vulcanization process reducing the thermal volatilization loss of liquid olefins during processing, while the inner layer liquid in the gradient distribution structure was effectively coated by the rubber network, reducing the migration and loss rate.
[0076] Comparative Example 2, used as the benchmark for flowability index (100), employed an extruder process to achieve better liquid dispersion uniformity than Comparative Example 1. However, the liquid olefins were still added in a single step, failing to form a gradient distribution, resulting in insufficient anchoring effect of the crosslinked network on the liquid. Furthermore, the sealant adhered to the inner surface of the tire in the form of a coating, exhibiting interface defects and prone to overall flow at high temperatures. Therefore, although its flowability index (100) was higher than that of Comparative Example 1 (95), it was lower than that of Examples 1-4 (110-145); the liquid retention rate (82%) was also lower than that of Examples 1-4 (88%-95%).
[0077] Comparative Example 1 used a traditional one-time mixing process in an internal mixer, resulting in uneven dispersion of liquid olefins, an incomplete crosslinking network, and easy flow deformation of the rubber compound under high-temperature shear. Furthermore, the traditional high-temperature vulcanization process led to significant evaporation loss of liquid components, resulting in the lowest liquid retention rate. Although the liquid dosage of Comparative Example 1 (35 kg) was higher than that of Example 2 (30 kg) and Example 4 (5 kg), its flowability index (95) was lower than that of Example 2 (135) and Example 4 (110), indicating that the step-by-step addition process is generally effective in improving flow resistance. This is because the excessive liquid added in Comparative Example 1 at one time did not form a gradient distribution, and a large amount of it remained outside the rubber matrix, making it more prone to overall sliding migration at high temperatures. In contrast, Example 2 had a higher liquid dosage, a more sufficient gradient distribution, and, combined with the anchoring effect of the uniform crosslinking network on the liquid, significantly improved flow resistance. Although the liquid dosage of Example 4 was at the lower limit (50 parts), the gradient distribution formed by the step-by-step addition still effectively suppressed the migration of free liquid, resulting in better flow resistance than Comparative Example 1, which added liquid olefins at one time. Liquid retention also follows the same intrinsic mechanism: the evaporation migration path of liquids wrapped in the gradient distribution is blocked, resulting in higher stability; while free liquids are more prone to evaporation and loss.
[0078] Comparative Example 3 uses a system of brominated butyl rubber and natural rubber, and adds chlorosulfonated polyethylene rubber with a high modulus, which makes the matrix more rigid. Therefore, the flowability index (120) is higher than that of Example 4 (110) where the liquid content is at the lower limit. However, no liquid olefins are added to its formulation, and it lacks a gradient distribution structure to further optimize the matrix modulus. It also does not have a self-healing function. Therefore, its flowability index is lower than that of Example 1-3 (135-145).
[0079] Test Example 3 Microstructure and fundamental thermal conductivity properties To evaluate the high-temperature stability and durability of the puncture-resistant self-healing tire inner liner rubber of the present invention, the relative crosslinking density and thermal conductivity of the puncture-resistant self-healing tire inner liner rubber in Examples 1-4 and the tire inner liner rubber in Comparative Examples 1-3 were tested. The specific test methods are as follows: (1) Crosslinking density relative value test Crosslinking density is a core parameter characterizing the perfection of the three-dimensional network structure of vulcanized rubber, directly affecting the elastic modulus, permanent deformation rate, heat resistance, and the binding capacity of liquid components in self-healing compounds. If the crosslinking density is too low, the rubber strength is insufficient, and the liquid olefin components are prone to macroscopic migration; if the crosslinking density is too high, the rubber is too hard, and the microscopic flowability required for self-healing is limited.
[0080] The equilibrium swelling method was employed, based on the Flory-Rehner lattice model theory. The equilibrium swelling degree of the vulcanizate in a good solvent was measured, the volume fraction of the rubber phase was calculated, and the crosslinking density was then determined. Using the crosslinking density of Comparative Example 1 as a reference, the relative values of the crosslinking densities for each experimental group were calculated.
[0081] Take the fully vulcanized puncture-resistant self-healing tire inner liner rubber from each experimental group and cut it into approximately 1mm × 1mm × 1mm samples. Three parallel samples should be prepared for each group. The samples should be free of visible pores, impurities, and defects. Conduct the tests according to the following steps: Dry the sample pieces in a vacuum drying oven at 60℃ until constant weight (the difference between two consecutive weighings is less than 0.1 mg), and accurately weigh the dried sample. m 2 (unit: g).
[0082] After drying, place the sample into a stainless steel mesh bag and then into a ground glass stoppered wide-mouth bottle containing sufficient toluene (analytical grade, purity ≥99.5%), ensuring that the sample is completely submerged.
[0083] Allow to swell at room temperature (23±2℃) for 72 hours, replacing the toluene every 24 hours.
[0084] After swelling is complete, remove the mesh bag, quickly absorb the toluene adhering to the sample surface with filter paper, and immediately weigh the swollen sample. m1 (unit: g).
[0085] The swollen sample was placed again in a 60℃ vacuum drying oven and dried to constant weight. The mass of the dried sample was then recorded. m 2' (unit: g), compared with the dry mass before swelling m 2. Comparison: If the mass change is less than 5%, then adopt... m 2 is used as the mass of the rubber skeleton; otherwise, it is adopted. m 2'.
[0086] Calculate the volume fraction of the rubber phase using the following formula ( V r ,%) crosslinking density (ν e mol / cm 3 ) and relative values of crosslinking density: ; in: ρ r This indicates the density of rubber (g / cm³). 3 For butyl rubber, the value is 0.92; for conjugated diene rubber, the value is 0.91; and the composite system is weighted averaged by mass fraction. ρ s Toluene density (g / cm³) 3 ), take 0.865 ; m 1 represents the mass (g) of the sample after swelling; m 2 represents the mass (g) of the rubber skeleton after drying.
[0087] ; in: χ represents the rubber-solvent interaction parameter, which is 0.56 for the butyl rubber-toluene system and 0.393 for the natural rubber-toluene system. The composite system is weighted by mass fraction. V s To represent the molar volume of toluene (cm³) 3 / mol), take 106.5.
[0088] ; in: ν e The crosslinking density (mol / cm³) of Examples 1-3, Comparative Examples 2 and 3 is indicated. 3 ); ν e,ref The crosslinking density of Comparative Example 1 is expressed in mol / cm³.3 ).
[0089] Take the arithmetic mean as the final result.
[0090] (2) Thermal conductivity test Thermal conductivity (thermal conductivity coefficient) is a physical quantity that characterizes the heat conduction ability of a material. For self-sealing tires, good thermal conductivity helps to conduct and dissipate the heat generated by tread friction and flexural deformation in a timely manner, avoiding excessive heat accumulation in the tread area, which can lead to accelerated aging of the rubber compound, failure of self-sealing components, or premature tire damage.
[0091] According to GB / T 32064-2024 "Determination of Thermal Conductivity of Vulcanized Rubber or Thermoplastic Rubber - Heat Flow Method", the heat flow method (steady-state hot plate method) was used, and the thermal conductivity was tested using a heat flow thermal conductivity meter.
[0092] Take the fully vulcanized puncture-resistant self-healing tire inner liner rubber from the experimental group and cut it into circular pieces with a diameter of 50 mm and a thickness of 3-5 mm. Five parallel samples should be prepared for each group. The upper and lower surfaces should be flat, smooth, parallel, and free of bubbles and impurities. Conduct the test according to the following steps: The sample was placed between the hot and cold plates and a pressure of 0.5 MPa was applied. The hot plate temperature is set to 30°C, and the cold plate temperature is lower than that of the hot plate (usually set to 20°C), forming a stable temperature gradient.
[0093] After the heat flow stabilizes (approximately 30-60 minutes), record the heat flow rate Q (unit: W) through the sample and the temperature difference ΔT (unit: °C) across the sample.
[0094] Measuring sample thickness d (Unit: m, average of 5 different locations), calculate the sample area. A (Unit: m) 2 ).
[0095] Calculate the thermal conductivity λ (W / (m·℃)) using the following formula: ; in: Q This represents the heat flow (W) through the sample under steady-state conditions. d Indicates the average thickness of the sample (m); A The effective heat transfer area of the sample (m²) 2 ); Δ T This indicates the temperature difference between the upper and lower surfaces of the sample (the difference between the hot plate temperature and the cold plate temperature) (°C).
[0096] Take the arithmetic mean as the final result.
[0097] The test results are shown in Table 3 below: Table 3. Relative values of crosslinking density and thermal conductivity test results for samples in each experimental group.
[0098] Note: With Comparative Example 1 as the baseline value of 100, a higher relative crosslinking density indicates a more complete vulcanization network structure. A higher thermal conductivity indicates better thermal conductivity of the rubber compound.
[0099] It can be seen from Table 3 above: The relative crosslinking densities of the samples in Examples 1-4 were 130, 125, 135, and 115, respectively, all superior to those of Comparative Example 1 (100) and Comparative Example 2 (105). Examples 1-3 were superior to Comparative Example 3 (115), while Example 4 was on par with Comparative Example 3. This improvement is mainly attributed to the synergistic controlled-release effect of the metal oxide-accelerator composite vulcanization package: the slow release of the accelerator allows the vulcanization reaction to proceed gradually, resulting in a more uniform distribution of crosslinking points; low-temperature, long-term vulcanization avoids network defects caused by excessively rapid crosslinking reactions at high temperatures. The uniform crosslinking network not only improves mechanical properties but also contributes to the stable dispersion of liquid olefins in the matrix. The thermal conductivity of the samples in Examples 1-4 were 0.30 W / m·℃, 0.28 W / m·℃, 0.31 W / m·℃, and 0.26 W / m·℃, respectively. Although these were lower than the thermal conductivity of Comparative Example 3 (0.32 W / m·℃ due to the addition of carbonyl iron powder to enhance thermal conductivity), they were within the typical thermal conductivity range of tire inner liner rubber (0.1-0.5 W / m·℃), meeting the actual application requirements.
[0100] Comparative Example 1 (100) serves as the benchmark for the relative value of crosslinking density. It employs a traditional one-time mixing process using an internal mixer, resulting in uneven dispersion of liquid olefins, uneven distribution of the components of the vulcanization system (vulcanizing agent, vulcanization accelerator, and zinc oxide) in the rubber compound, insufficient crosslinking reaction, numerous network structure defects, and the lowest relative value of crosslinking density. Furthermore, its formulation does not incorporate thermal conductivity design.
[0101] The dispersion of the vulcanizing agent in Comparative Example 2 was improved due to the mixing in the extruder, but it used a dicumyl peroxide combined with zinc oxide vulcanization system, which lacked a synergistic controlled release mechanism. The crosslinking reaction rate was fast and the network uniformity was insufficient. The relative value of the crosslinking density (105) was lower than that of Example 1-4 (115-135); the thermal conductivity was also not specifically designed.
[0102] Comparative Example 3 uses a conventional vulcanization system (composed of sulfur, vulcanization accelerator and zinc oxide) with a high amount of accelerator (1.5 kg), so that its relative crosslinking density (115) is comparable to that of Example 4 (115). However, due to the lack of the slow-release effect of the composite vulcanization package of the present invention, the uniformity of the crosslinking network is insufficient, and the relative crosslinking density is lower than that of Examples 1-3 (125-135). The thermal conductivity reaches 0.32 W / m·℃ due to the introduction of carbonyl iron powder, which is higher than that of Examples 1-4 (0.26-0.31 W / m·℃). However, no liquid olefins are added to its formulation, so it does not have a self-healing function.
[0103] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a puncture-resistant, self-healing tire inner liner rubber, characterized in that, Includes the following steps: S1. After mixing butyl rubber and conjugated diene rubber, plasticize for 2-4 minutes, add reinforcing filler, resin and homogenizer, mix at 100-130℃ for 5-8 minutes, discharge the rubber, and obtain masterbatch. S2. Cool the masterbatch obtained in step S1 to 40-60℃, add 30%-50% of the total amount of liquid olefin compounds, and keep it warm while stirring for 20-40 minutes; heat the system to 80-100℃, add the remaining liquid olefin compounds, and continue to mix for 10-20 minutes to obtain the pre-dispersed rubber compound. S3. Add vulcanizing agent and composite vulcanizing package to the pre-dispersed rubber compound obtained in step S2, and mix at 60-80℃ for 3-5 minutes to obtain two-stage compounded rubber. S4. The two-stage compound obtained in step S3 is left to stand for 8-24 hours at a temperature of 20-30℃ and a relative humidity of 40%-60%. Finally, it is vulcanized for 60-120 minutes at a pressure of 0.5-2MPa and a temperature of 70-90℃ to obtain puncture-resistant self-healing tire inner liner rubber.
2. The preparation method according to claim 1, characterized in that, The composite vulcanizing package described in step S3 is prepared by mechanically mixing metal oxide powder and vulcanization accelerator at a mass ratio of (2-10):(1-5) for 5-10 minutes at room temperature.
3. The preparation method according to claim 1, characterized in that, The puncture-resistant, self-healing tire inner liner rubber is composed of the following raw materials in parts by weight: 80-100 parts of butyl rubber; 0-20 parts of conjugated diene rubber; 50-500 parts of liquid olefin compounds; 3-15 parts of composite vulcanizing package; 1-15 parts of vulcanizing agent; 0-50 parts of resin; 5-70 parts of reinforcing filler; 2-8 parts homogenizer.
4. The preparation method according to claim 3, characterized in that, The liquid olefin compound is selected from one or more of polyisobutylene, polyisoprene, or polybutadiene.
5. The preparation method according to claim 4, characterized in that, The number-average molecular weight of the liquid olefin compounds is 500-5000 g / mol.
6. The preparation method according to claim 2, characterized in that, The metal oxide powder is selected from one or more of zinc oxide, magnesium oxide, or calcium oxide; the sulfidation accelerator is selected from one or more of thiuram accelerators, thiazole accelerators, or sulfenamide accelerators.
7. The preparation method according to claim 6, characterized in that, The particle size D50 of the metal oxide powder is 0.5-5 μm.
8. The preparation method according to claim 3, characterized in that, The conjugated diene rubber is selected from one or more of natural rubber, butadiene rubber, polyisoprene rubber, or styrene-butadiene rubber; the vulcanizing agent is sulfur; the resin is selected from one or more of C5 resin, C9 resin, C5 / C9 resin, rosin resin, terpene resin, DCPD resin, phenolic resin, or coumarone-indene resin; the reinforcing filler is selected from one or more of carbon black or silica; the homogenizing agent is selected from one or more of aromatic hydrocarbon resin mixtures, aliphatic hydrocarbon resin mixtures, or aromatic hydrocarbon-aliphatic hydrocarbon blends.
9. The application of the puncture-resistant self-healing tire inner liner rubber prepared by the preparation method according to any one of claims 1-8 in tire production.
Citation Information
Patent Citations
Sealant for self-repairing tire, preparation method of sealant, and self-repairing tire
CN114058293A
Inner liner rubber composition, preparation method thereof and tire inner liner
CN120310149A